2018
DOI: 10.17925/enr.2018.13.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Pattern of Craniofacial Pain and Headache in Danish Patients with Neuromyelitis Optica Spectrum Disorder

Abstract: There is a dearth of knowledge about the pattern of pain and somatosensory alterations that co-exist with neuromyelitis optica spectrum disorder (NMOSD). Understanding the presence and underlying mechanisms will assist in better pain management in these patients. This study sought to identify prevalence and pattern of headache, craniofacial pain and abnormalities in somatosensory function within a group of NMOSD patients in Denmark. Six patients (two males, four females; mean age 41.2 ± 8.6 years) participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(101 reference statements)
0
1
0
Order By: Relevance
“…Several previous case studies have reported that NMOSD patients presented choreoathetosis or pseudoathetosis, a series of involuntary and irregular movements of the face, head, hand or limbs (Boddu and Shenker 2019; Seok, Jang, and You 2018; Sugeno 2013). In addition, headaches and craniofacial pain were reported in NMOSD patients (Nielsen et al 2018). Since cortical thinning typically reflects neuron loss and functional deficits, the thinner PMB is speculated to, at least partly, be responsible for these symptoms in NMOSD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous case studies have reported that NMOSD patients presented choreoathetosis or pseudoathetosis, a series of involuntary and irregular movements of the face, head, hand or limbs (Boddu and Shenker 2019; Seok, Jang, and You 2018; Sugeno 2013). In addition, headaches and craniofacial pain were reported in NMOSD patients (Nielsen et al 2018). Since cortical thinning typically reflects neuron loss and functional deficits, the thinner PMB is speculated to, at least partly, be responsible for these symptoms in NMOSD patients.…”
Section: Discussionmentioning
confidence: 99%